The Impact of Telemedicine Adoption on a Multidisciplinary Bariatric Surgery Practice During the COVID-19 Pandemic. Issue 6 (December 2020) - Brown, Andrew M.; Ardila-Gatas, Jessica; Yuan, Victoria; Devas, Nina; Docimo, Salvatore; Spaniolas, Konstaninos; Pryor, Aurora D.
Abstract : Objective: This study aims to show how full-time telemedicine adoption has impacted patient visit volume and attendance in a comprehensive metabolic and weight loss center. Summary Background Data: Elective surgical practices have been profoundly impacted by the global COVID-19 pandemic, leading to a rapid increase in the utilization of telemedicine. The abrupt initiation of audio-video telehealth visits for all providers of a multidisciplinary clinic on March 19 th 2020 provided unique circumstances to assess the impact of telemedicine. Methods: Data from the clinical booking system (new patient and follow-up visits) for all clinical provider types of the multidisciplinary metabolic center from the pre-telehealth, post-telehealth, and a 2019 comparative period were retrospectively reviewed and compared. The primary outcome is the change in patient visit volume for all clinical providers from before to after the initiation of telemedicine for both new patient, and follow-up visits. Results: There were a total of 506 visits (162 new patient visits, and 344 follow-ups) in the pre-telehealth period, versus 413 visits (77 new patient visits, and 336 follow-ups) during the post-telehealth period. After telehealth implementation, new visits for surgeons decreased by 75%. Although follow-up visits decreased by 55.06% for surgeons, there was an increase by 27.36% for advanced practitioners. When surgeons were separated from other practitioners, their follow-up visit rate decrease by 55.06%, compared to a 16.08% increase for the group of all other practitioners ( P < 0.0001). Dietitians experienced higher rates of absenteeism with new patient visits (10.00% vs 31.42%, P = 0.0128), whereas bariatricians experienced a decrease in follow-up visit absenteeism (33.33% vs 0%, P = 0.0093). Conclusions: Although new patient visit volume fell across the board, follow-up visits increased for certain nonsurgical providers. This provides a template for adoption of a multidisciplinary telehealth clinic in a post-pandemic world.